How we treat paroxysmal nocturnal hemoglobinuria: A consensus statement of the Canadian PNH Network and review of the national registry. (25th October 2018) - Patriquin, Christopher J.; Kiss, Thomas; Caplan, Stephen; Chin‐Yee, Ian; Grewal, Kuljit; Grossman, Jennifer; Larratt, Loree; Marceau, Daniele; Nevill, Tom; Sutherland, D. Robert; Wells, Richard A.; Leber, Brian
Abstract: Paroxysmal nocturnal hemoglobinuria (PNH) is a rare hematologic disease characterized by intravascular hemolysis, thrombophilia, and marrow failure. Its phenotype is due to absent or reduced expression of GPI‐linked complement regulators and subsequent sensitivity of hematopoietic cells to complement‐mediated damage and lysis. Introduction of the terminal complement inhibitor eculizumab drastically improved outcomes in PNH patients; however, despite this improvement, there remain several challenges faced by PNH patients and physicians who care for them. One of the most important is increasing awareness of the heterogeneity with which patients can present, which can lead to significant delays in recognition. Data from the Canadian PNH Registry are presented to demonstrate the variety of presenting symptoms. In Canada, geography precludes consolidation of care to just a few centers, so management is distributed across academic hospitals, linked together as the Canadian PNH Network. The Network over the last several years has developed educational programs and clinical checklists and has worked to standardize access to diagnostics across the country. Herein, we address some of the common diagnostic and therapeutic challenges faced by PNH physicians and give our recommendations. Gaps in knowledge are also addressed, and where appropriate, consensus opinion is provided.